2005
DOI: 10.2190/w346-up8t-rer6-bbd1
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Bereavement Processes of Older Parents: The Three Phases of Grief

Abstract: This study is based upon personal interviews with 47 elderly bereaved parents. These interviews provided us with detailed and extensive information on the bereavement processes that parents experience over a long period of years. From an in-depth content analysis of the interviews and the way the parents described bereavement, it seems that it is a central motif in their lives affecting their relationships with each other, with the living children, with friends, at work and with others. Although enduring grief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
(21 reference statements)
2
43
0
1
Order By: Relevance
“…Insofar as a child's development largely depends on the quality of the attachment relationship with his or her parent(s), being a parent is an underestimated developmental achievement for many persons that can engender a sense of identity and purpose (Rubin & Malkinson, 2001). Therefore, when a child dies, many parents not only experience sadness over losing a valued member of the family; they feel that a part of themselves has somehow died as well (Malkinson & Bar-Tur, 2005). Although the majority of bereaved parents find a way to resume productive lives, studies have shown that grief symptoms for parents who outlive their children frequently endure throughout the life span (Dyregrov & Dyregrov, 1999;Lehman, Wortman, & Williams, 1987;Malkinson & Bar-Tur, 2005;Martinson, Davies, & McClowry, 1991;Rubin, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insofar as a child's development largely depends on the quality of the attachment relationship with his or her parent(s), being a parent is an underestimated developmental achievement for many persons that can engender a sense of identity and purpose (Rubin & Malkinson, 2001). Therefore, when a child dies, many parents not only experience sadness over losing a valued member of the family; they feel that a part of themselves has somehow died as well (Malkinson & Bar-Tur, 2005). Although the majority of bereaved parents find a way to resume productive lives, studies have shown that grief symptoms for parents who outlive their children frequently endure throughout the life span (Dyregrov & Dyregrov, 1999;Lehman, Wortman, & Williams, 1987;Malkinson & Bar-Tur, 2005;Martinson, Davies, & McClowry, 1991;Rubin, 1990).…”
mentioning
confidence: 99%
“…Therefore, when a child dies, many parents not only experience sadness over losing a valued member of the family; they feel that a part of themselves has somehow died as well (Malkinson & Bar-Tur, 2005). Although the majority of bereaved parents find a way to resume productive lives, studies have shown that grief symptoms for parents who outlive their children frequently endure throughout the life span (Dyregrov & Dyregrov, 1999;Lehman, Wortman, & Williams, 1987;Malkinson & Bar-Tur, 2005;Martinson, Davies, & McClowry, 1991;Rubin, 1990). However, few studies have sampled bereaved parents with substantial variability in times since loss or examined several of the more clinically relevant factors that could be crucial to identifying the subset of bereaved parents who may benefit from a psychotherapeutic intervention (see Schut, Stroebe, van den Bout, & Terheggen, 2001, for review).…”
mentioning
confidence: 99%
“…Malkinson and Bar-Tur (2005) report that the moment of notification of a child's loss is often remembered, even decades later, in minute detail, with intense emotions and somatic reactions similar to those observed in posttraumatic distress. A recent study showed that the violence of the death and the age of the child at death accounted for significant differences in normative grief symptoms.…”
mentioning
confidence: 99%
“…The loss of children affects others for much longer than the loss of other loved ones, and particularly affects parents throughout their remaining life (Malkinson & Bar-Tur, 2004). Child loss is associated with psychiatric illnesses, existential pain, marital problems, and even increased mortality .…”
Section: Studying Bereaved Parents Using the Spiritually Orientated Mmentioning
confidence: 99%